A multi-evaluating strategy for raw and processed Veratrum nigrum L.: Fingerprinting combined with quantitative analysis based on multivariate chemometric methods - Guangzhe Yao; Mengxuan Wu; Minglei Ge; Mengmeng Zhang; Xiunan Cao; Yameng Zhu; Shujie Wei; Yanxu Chang; Huizi Ouyang; Jun He (Arabian Journal of Chemistry, 2023)
Veratrum nigrum L. (VN) is a well-known herbal medicine and rich in chemical components with multiple pharmacological activities including antihypertensive, anticancer, and antifungal effects. In the current experiment, the quality of VN from different habitats was evaluated based on combinative method of fingerprint, multi-component quantification and chemical pattern recognition. Fifteen batches of VN were collected, and intrinsic chemical composition were identified using ultra-performance liquid chromatography coupled with quadrupole time-of-flight mass spectrometry, which is a method for analyzing the similarity between samples, coupled with fingerprint of traditional Chinese medicine. The fingerprint similarity model show that 22 common peaks were selected covering 15 batches of and the similarity > 0.963. The total of 22 joint components were tentatively identified by comparison with standard substances or literature. A ultra-high performance liquid chromatography coupled with triple quadrupole mass spectrometry method for simultaneous determination of 8 compounds was established to evaluate the contents of raw and processed Veratrum nigrum L. Multivariate analysis was then applied to compare different batches of herbs based on ultra-high performance liquid chromatography coupled with triple quadrupole mass spectrometry data. All raw and processed samples were classified by partial least squares discriminant analysis based on the 8 analyzed compounds. The findings suggested that veratramine and polydatin with a variable importance for the project (VIP) > 1 were identified as significant constituents, the presence of which can be used to differentiate between raw and processed Veratrum nigrum L. samples. These results indicate that processing methods show important effects on the composition of Veratrum nigrum L..